Evaluation of intrauterine pathologies by hysteroscopy in abnormal uterine bleeding - Sonam Dhakad; Sandhya Gadre; Gunjan Chaudhary (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Hysteroscopy is the gold standard for uterine cavity evaluation because it allows direct visualization of the uterine cavity, mitigate characteristics of lesions such as nature, size, shape, location and vascular pattern. Methods: This was a prospective observational study conducted in department of obstetrics and gynecology at Chirayu Medical College and Hospital, Bhopal (MP). Patients presenting to general gyne OPD with abnormal uterine bleeding at Chirayu Medical College and Hospital between January 2021 to May 2022 were studied. All patients selected for study had a thorough evaluation with detailed history, clinical examination, lab tests and sonography followed by hysteroscopy and endometrial biopsy. Results: Mean age of patients in our study was 44 years with majority of patients in 41-50 years age group. Predominant complaint reported was heavy menstrual bleeding (HMB) (47.50%) followed by HMB with frequent cycle (11.25%). Hysteroscopy detected intrauterine abnormality in 42.50% cases. Most common finding on hysteroscopy in our study was hyperplastic endometrium in 17.50% patients followed by endometrial polyp in 15% of patients. Atrophic endometrium was seen in 2.5% and 2.5% had submucous fibroid. Conclusions: Hysteroscopy allows diagnosis or exclusion of intracavitary pathologies, which are underdiagnosed on routine pelvic sonography. It also enables treatment in the same sitting with accurate tissue biopsy from the representative areas and facilitates planning of further management. When combined with endometrial biopsy and pelvic ultrasonography, it can establish an accurate diagnosis in a majority of patients thereby reducing the burden of hysterectomy.